Multilevel Analysis: Village Does Not Have Contextual Effect on Hepatitis A Outbreak in Pacitan, East Java, Indonesia - Retyono, Sugeng; Rahardjo, Setyo Sri; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Hepatitis A virus infection (HAV) has generated about half of the total infection of hepatitis in the world. Poor envi